Do voters prefer logrolling to compromise in parliamentary democracies? - Ecker, Alejandro; Meyer, Thomas M.; Plescia, Carolina (Electoral studies, 2025)
In countries ruled by coalition governments, government policy is the result of negotiations between parties with diverging policy positions. We study what type of deals voters are willing to accept in these negotiations: policy compromises on individual issues or logrolls where each party gets to keep its position on one issue while conceding on another one. Based on a pre-registered survey experiment conducted after the 2021 Dutch general election, we find no evidence that respondents prefer logroll deals over policy compromises per se. Yet, voters are more sensitive to their policy preferences when evaluating logroll compared to compromise deals. In additional analyses, we show that this logroll effect is more pronounced when the logroll allows parties to keep their positions on their respective core issues. Our results have wider implications for political representation and government formation processes.
Gesehen am 28.03.2025
Online veröffentlicht: 14. Dezember 2024